КЛАССИФИКАЦИЯ КОНФЛИКТОВ: ПРАВОВОЙ АНАЛИЗ (Journal of actual problems of jurisprudence, 2019)
This article focuses on the classification of conflict in society and legal analysis. Especially the classification criteria for conflict, on aspects ofneeds, on time, on the impact and the volume of social interaction. Considered a typology of legal conflicts, depending on the nature of the relevantlegal norms.